PENGARUH CONTENT MARKETING DAN INFLUENCER MARKETING TERHADAP INTERAKSI KONSUMEN MELALUI MEDIA SOSIAL INSTAGRAM ( Studi Kasus Pada Konsumen Produk Scarlett Whitening di Kabupaten Lamongan): (Studi Kasus pada Konsumen Produk Scarlett Whitening di Kabupaten Lamongan) - Zyadatul Inayah, Adinda; Shofia Maulida, Indira; Susanti, Ike; Efendi, Yuhronur (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
This research aims to analyze the influence of Content Marketing and Influencer Marketing on Consumer Interaction with Scarlett Whitening Products via Instagram social media. The type of research used is descriptive quantitative research. The population in this study was 5,500,000 taken from Scarlet Whitening Instagram followers in general with a sample size of 100 consumers who are consumers of Scarlett Whitening products in Lamongan Regency. Data collection techniques by distributing questionnaires to respondents. The data analysis used is SMART PLS. This research begins in November 2023 to March 2024. From the results of this research it can be concluded that the Content Marketing Variable partially has a significant effect on Consumer Interaction for Scarlett Whitening products via Instagram Social Media with an Original Sample value (coefficient) of 0.134 > 0.000. T-Statistic (1.665) > T Table (1.64). P Value (0.045 < 0.05). The Influencer Marketing variable partially has a significant effect on Consumer Interaction for Scarlett Whitening products via Instagram Social Media with an Original Sample value (coefficient) of 0.168 > 0.000. T-Statistic (1.777) > T Table (1.64). P Value (0.038 < 0.05). It was concluded from the results of the R Square test that the joint influence of Content Marketing and Influencer Marketing on consumer interaction was 0.586 with an Adjusted R Square value of 0.573. The most dominant variable was Content Marketing on Consumer Interaction with a value of 0.392.